Dimensions of Talent Management and Employee Retention: A study in the Financial field - Shrestha , Rohit Kumar; Dhakal , Bhakta Prasad (Sahayaatra सहयात्रा, 2026)
Talent management is defined as identifying, attracting, engaging, providing training, developing, advancing, and keeping up with qualified people. The major objective of the study is to assess the status of dimensions of talent management i. e., talent attraction and employee engagement on employee retention in the financial institution of Nepal. The study applied a descriptive research design and convenience sampling technique. The sample size was 485 for the study. In this study, male respondents outnumbered female ones. Among all employees, operating level employees are the most followed by the supervisory and the managerial levels in the organizations. By age group, older people were in the lowest per cent and vice versa. As far as the level is concerned, there is the highest per cent of employees in the operating level and are followed by supervisory and managerial. By the organization, there is the highest number or per cent of employees working in Agriculture Development Bank and are followed by Kamana Sewa Bikas Bank Ltd., Nabil Bank, Rastriya Jeewan Beema Company and National Life Insurance Company. The current state of items or statements of talent attraction indicates that the mode pushes toward agreement. However, in a few items mode pushes toward indifference. Except for only one item for employee engagement, the mode pushes toward agreement in all items. It is recommended that financial institutions should invest in the sector of talent management to attract and engage the employees. It is suggested to carry out further research studies on non-financial sectors such as manufacturing, trading, social and securities.